The Effect of Filial Therapy on the Parenting Stress of Mothers of Children With Autism Spectrum Disorder - Zahra Kiyani; Hoshang Mirzai; Seyed Ali Hosseini; Hossein Sourtiji; Samaneh Hosseinzadeh; Elahe Ebrahimi (University of Social Welfare and Rehabilitation Sciences, 2020)
Objective: Autism Spectrum Disorder (ASD) is a neurodevelopmental disorder that affects the person' life. The prevalence of ASD in Iran is increasing. The complicated nature of this disorder disrupts the balance and work routines in the family, which puts a lot of stress on the entire family, especially mothers. Mental health of the mother affects all family members, including a child with ASD. On the other hand, mothers' confusion and failure in relation to their ASD child causes more stress and discomfort for them. In this study, we aimed to investigate the effect of filial therapy, as a play therapy, on the parenting stress of mothers with ASD children. Materials & Methods: In this experimental study, participants were the mothers of 32 children with ASD (9 girls and 23 boys) aged 4-12 years referred to autism centers and occupational therapy clinics in Isfahan, Iran who were selected using a convenience sampling method. After obtaining an ethical approval from the Research Ethics Committee of the University of Social Welfare and Rehabilitation Sciences (code: IR.USWR.REC.1396.97), and necessary permissions, researchers referred to the clinics and after explaining the purpose of the study to the mothers, an informed consent was obtained from them. Then, they completed a demographic form, Gilliam Autism Rating Scale-2 (GARS-2), and Abidin's Parenting Stress Index-Short Form (PSI-SF). Participants were randomly divided into two intervention and control groups after matching for the child's age, GARS score, and the education of children and mothers. The intervention group received 10 sessions of filial therapy, once a week, each for two hours, while the control group continued routine treatment. After intervention, PSI-SF was completed by all mothers again. The collected data were analyzed by using ANCOVA, paired t-test and independent t-test. Shapiro-Wilk test was used to determine the normality of PSI-SF data distribution at Pre-test and Post-test phases. Results: Paired t-test results showed that there was no statistically significant difference in the mean total parenting stress score between the two groups in the Pre-test phase (P= 0.679) but it was significant in the Post-test phase (P=0.010). The results of independent t-test showed that the difference between the mean Pre-test and Post-test scores of total parenting stress in the control group was not significant (P= 0.268) but it was significant in the intervention group (P=0.001). ANCOVA results showed that the Pre-test score of parenting stress had an effect on the total parenting stress score after intervention such that it could explain 82% of variations in this variable. After controlling the Pre-test score, the total parenting stress was significantly different in two groups (P=0.001). Eta squared value indicated that the intervention could explain 54% of changes in total parenting stress of mothers. Conclusion: Filial therapy can help better acceptance of the ASD children by their parents and reduce parenting stress by improving child-parent relationships. This method can be taught as a complementary intervention to the mothers of ASD children.